2003
DOI: 10.1002/mrc.1198
|View full text |Cite
|
Sign up to set email alerts
|

Non‐empirical calculations of NMR indirect carbon–carbon coupling constants. Part 4: Bicycloalkanes

Abstract: A systematic study of the one-bond and long-range J(C,C), J(C,H) and J(H,H) in the series of nine bicycloalkanes was performed at the SOPPA level with special emphasis on the coupling transmission mechanisms at bridgeheads. Many unknown couplings were predicted with high reliability. Further refinement of SOPPA computational scheme adjusted for better performance was carried out using bicyclo[1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 110 publications
1
17
0
Order By: Relevance
“…Furthermore, in one of the previous papers 4 in this series, it was unambiguously demonstrated that geometric factors play only a minor role in the calculations of…”
Section: Cyclooctane (6)mentioning
confidence: 83%
See 4 more Smart Citations
“…Furthermore, in one of the previous papers 4 in this series, it was unambiguously demonstrated that geometric factors play only a minor role in the calculations of…”
Section: Cyclooctane (6)mentioning
confidence: 83%
“…The latter may arise from the non-bonded interactions of those carbons such as that involving bridgehead carbons in bicyclo[1.1.1]pentane (separated by ca 1.9Å), as manifested in the series of papers by Barfield and co-workers 107 and later by Contreras and co-workers 108 and well reproduced in our previous SOPPA calculations. 4 Unfortunately, both methods, SOPPA and SOPPA(CCSD), slightly overestimate this interesting coupling, giving ca 10 to 11 Hz compared with the experimental value of ca 8 Hz. 109 Vicinal couplings are ca C2 Hz in cyclohexane (4) and near zero (<0.2 Hz) in larger monocycloalkanes 5 and 6, which is due to the Karplus dependence of 3 J(C,C): the dihedral angles of the coupling paths are ϕ D 54.4°in 4, 85.7°i n 5 and 100.2°in 6, corresponding to a gauche arrangement of the coupled carbons in 4 and a near orthogonal arrangement in 5 and 6.…”
Section: Carbon-carbon Couplings In Monocycloalkanesmentioning
confidence: 93%
See 3 more Smart Citations